Effect of dietary fiber fermentation on short‐chain fatty acid production and microbial composition in vitro. (20th May 2020) - Bai, Yu; Zhao, Jin‐biao; Tao, Shi‐yu; Zhou, Xing‐jian; Pi, Yu; Gerrits, Walter JJ; Johnston, Lee J; Zhang, Shi‐yi; Yang, Hong‐jian; Liu, Ling; Zhang, Shuai; Wang, Jun‐jun
Abstract: BACKGROUND: The efficient utilization of fiber‐rich co‐products is important for optimizing feed resource utilization and animal health. This study was conducted to evaluate the fermentation characteristics of fiber‐rich co‐products, which had equal quantities of total dietary fiber (TDF), at different time points using batch in vitro methods. It considered their gas production, short‐chain fatty acid (SCFA) production, and microbial composition. RESULTS: The fermentation of wheat bran (WB) and oat bran (OB) showed higher and faster ( P  < 0.05) gas and SCFA production than corn bran (CB), sugar beet pulp (SBP), and soybean hulls (SH). The α ‐diversity was higher in the CB, SBP, and SH groups than in the WB and OB groups ( P  < 0.05). At the phylum level, OB and WB fermentation showed lower ( P  < 0.05) relative abundance of Actinobacteria than the CB, SBP, and SH groups. At the genus level, OB and WB fermentation increased the Enterococcus population in comparison with the CB, SBP, and SH groups, whereas CB and SBP fermentation improved the relative abundance of the Christensenellaceae R‐7 group more than the WB, OB, and SH groups ( P  < 0.05). CONCLUSION: Overall, WB and OB were rapidly fermented by fecal microbiota, in contrast with SBP, SH, and CB. Fermentation of different fiber‐rich co‐products with an equal TDF content gives different responses in terms of microbial composition and SCFA production due to variations in their physicochemical properties and molecular structure. © 2020 Society of Chemical Industry